Pengaruh Self Efficacy, Karakter Wirausaha, dan Lingkungan Sosial Terhadap Intensi Berwirausaha Berbasis Digital pada Mahasiswa - Ghaida Widya Cantika; Putri Ulfa Kamalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Digital entrepreneurship can be one of the efforts to overcome the problem of educated unemployment in Indonesia. In the process of running a digital entrepreneurship, it is necessary to grow the intention to become an entrepreneur. This study aims to analyze the influence of self-efficacy, entrepreneurial character and social environment on the intention to become a digital-based entrepreneur in students. The research data derived from three instruments, namely self-efficacy, entrepreneurial character and social environment, were collected using a questionnaire instrument distributed to respondents. This study uses associative research with quantitative approach. The population in this study were undergraduate students of the economics education study program, Surabaya State University, class of 2020 and 2021. The research sample was determined using the simple random sampling technique and calculated using the slovin formula, so that the results showed that the research sample used in this study was 105 students. The results of this study indicate that (1) self-efficacy does not affect the intention of digital-based entrepreneurship in students (2) entrepreneurial character affects the intention of digital-based entrepreneurship in students (3) social environment affects the intention of digital-based entrepreneurship. Based on the R-square results of 0.657, it can be interpreted that the contribution of the independent variables used in this research to the dependent variable is 65.7%, so that the remaining 34.3% can be determined by other factors outside this research.